Prove the following identity -

\[\displaystyle \prod_{r=1}^{n}{\Gamma\left(\frac{r}{n+1}\right)} = \sqrt{\frac{{(2\pi)}^{n}}{n+1}}\]

Please be original. I hope you will not copy from sites like MSE(where it might be discussed).

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestProof:\(\because\sin(x) = \frac{1}{2i}(e^{ix}-e^{-ix})\)

\(\displaystyle\implies\prod_{k=1}^{n-1} \sin\left(\dfrac{k\pi}{n}\right) = \left(\dfrac{1}{2i}\right)^{n-1}\prod_{k=1}^{n-1} \left(e^{\frac{k\pi i}{n}} - e^{\frac{-k\pi i}{n}}\right)\)

\(\displaystyle= \left(\dfrac{1}{2i}\right)^{n-1} \ \left(\prod_{k=1}^{n-1} e^{\frac{k\pi i}{n}} \right) \prod_{k=1}^{n-1} \left(1-e^{\frac{-2k\pi i}{n}} \right)\)

\(\displaystyle= \left(\dfrac{1}{2i}\right)^{n-1} \times i^{n-1} \prod_{k=1}^{n-1} \left(1-e^{\frac{-2k\pi i}{n}} \right)\)

\(\displaystyle= \dfrac{1}{2^{n-1}} \prod_{k=1}^{n-1} \left(1-e^{\frac{-2k\pi i}{n}} \right)\)

Consider the factorisation,

\[x^{n-1}+x^{n-2}+ \ldots + x + 1 = \prod_{k=1}^{n-1}\left(x-e^{\frac{-2\pi k}{n}}\right)\]

Putting \(x=1\) in the above identity gives,

\( \displaystyle \prod_{k=1}^{n-1} \left(1-e^{\frac{-2k\pi i}{n}} \right)=n \)

\(\displaystyle \therefore \prod_{r=1}^{n-1}\sin\left(\dfrac{r\pi}{n}\right)=\dfrac{n}{2^{n-1}}\)

Now, consider

\[\text{S}=\sum_{r=1}^{n}\log \left(\Gamma{\left(\dfrac{r}{n+1}\right)}\right)\]

\(\displaystyle = \sum_{r=1}^{n}\log \left(\Gamma{\left(\dfrac{n+1-r}{n+1}\right)}\right) \ \left(\because \sum_{r=a}^{b}f(r)=\sum_{r=a}^{b}f(a+b-r)\right)\)

\(\displaystyle = \sum_{r=1}^{n}\log \left(\Gamma{\left(1-\dfrac{r}{n+1}\right)}\right)\)

By Euler's Reflection Formula,

\(\displaystyle \text{S} = \sum_{r=1}^{n}\log \left(\dfrac{\pi}{\Gamma{\left(\dfrac{r}{n+1}\right)}\sin \left(\dfrac{r\pi}{n+1}\right)}\right)\)

\(\displaystyle =\log ({\pi}^n) - \sum_{r=1}^{n}\log\left(\Gamma{\left(\dfrac{r}{n+1}\right)}\right) - \sum_{r=1}^{n} \log \left(\sin \left(\dfrac{r\pi}{n+1}\right)\right)\)

\(\displaystyle \implies 2\text{S} = \log({\pi}^n) - \sum_{r=1}^{n} \log \left(\sin \left(\dfrac{r\pi}{n+1}\right)\right)\)

Using the Lemma, we have,

\(2\text{S}=\log({\pi}^n) - \log\left(\dfrac{n+1}{2^n}\right)\)

\(\displaystyle \implies \text{S} = \log \left(\sqrt{\dfrac{(2\pi)^n}{n+1}}\right)\)

\(\displaystyle \implies \sum_{r=1}^{n}\log \left(\Gamma{\left(\dfrac{r}{n+1}\right)}\right) = \log \left(\sqrt{\dfrac{(2\pi)^n}{n+1}}\right)\)

\(\displaystyle \implies \log\left(\prod_{r=1}^{n}\Gamma{\left(\dfrac{r}{n+1}\right)}\right) = \log \left(\sqrt{\dfrac{(2\pi)^n}{n+1}}\right)\)

\[\boxed {\therefore \displaystyle \prod_{r=1}^{n}\Gamma{\left(\dfrac{r}{n+1}\right)}=\sqrt{\dfrac{(2\pi)^n}{n+1}}}\]

Log in to reply

Yep. That's correct! That is also the way I did it. I am curious to know if there is any other approach. Maybe using convolution theorem?

Log in to reply

Another way is to use the Multiplication Theorem. To prove the multiplication theorem, the limit definition of gamma function can be used.

Log in to reply

I don't understand what's the limit definition?

Log in to reply

Log in to reply

Log in to reply